(untitled) (Journal of Engineering, 2006)
Permanent deformations (rutting) of asphalt pavements which appear in many roads in Iraq. have caused a major impact on pavement performance by reducing the useful service life of pavement and creating services hazards for highway users. Therefore, it is important to analyze and investigate this type of distress. The objectives of the present paper include; the analysis of the main contributory factors influencing rutting, and development of statistical model for the prediction of permanent deformation in paving materials. To achieved these objectives for the requirements of data collection. five types of gradation. (40-50) asphalt cement and different types of filler are used to prepare three hundred sixty asphalt concrete specimens throughout the work using Marshall method and Superpave system. Most of these specimens are tested by applying diametric creep under different temperatures and stress levels.A statistical model has been developed for the prediction of rut depth in local asphalt paving materials as influencing by the factors of asphalt cement content, mineral filler type, air voids and environmental temperature